Effects of electrolytes on electrochemical behaviour and performance of Ti6Al4V alloy prepared by laser directed energy deposition - Jun Yu; Linzeng Wang; Guoqiang Kang; Xin Lin; Lijun Tian; Pengfei Guo; Liangyi Wu; Weidong Huang (Journal of Materials Research and Technology)
This study investigates the influence of electrolytes on the electrochemical (EC) performance of Ti6Al4V alloy fabricated via laser directed energy deposition (LDED). The EC dissolution efficiencies and surface roughnesses of the alloy are assessed, and the surface passivation films are analyzed through impedances, vacancy concentrations, compositions, and nanostructures. The results demonstrate that the NaCl + EDTA-2Na electrolyte attains a moderate EC machining efficiency and the optimal surface roughness of 0.31 μm at its best performance. Transmission electron microscopy reveals distinct dissolution variations between the α and β phases during ECM. The average film thickness on the α-phase is approximately 400 nm in NaCl + NaNO3 electrolyte, 35 nm in NaCl + EDTA-2Na electrolyte, and merely 10 nm in NaCl + NaBr electrolyte. Furthermore, the anionic effects on transpassive dissolution in different electrolytes are illustrated based on the point defect model. These findings reveal that, when compared to the NaCl + NaBr electrolyte, the average ECM efficiency in NaCl + EDTA-2Na drops by 4.3%, whereas the surface roughness experiences a significant reduction of 76.3%. Especially, the dissolution difference between α and β phases can be suppressed in NaCl + EDTA-2Na electrolyte. These insights can guide the selection of electrolytes for efficient and precise ECM of LDED-prepared dual-phase titanium alloy in industrial applications.